Etude de l’effet inhibiteur de l’acide salicylique sur l’adhérence et la croissance planctonique de Bacillus cereus et Staphylococcus aureus - BRAHIMI, HAYET; HATTOU, SOUMIA (My University, 2023)
Staphylococcus aureus and Bacillus cereus are opportunistic pathogens responsible for foodborne illness in part is due to their ability to colonize many biotic and abiotic surfaces. These persistent poisoning can be difficulte to treat because of a large virulence factor directory, and organizational capacity to form monitoring protocol biofilms.Le helped us and in a very clear way to demonstrate the rate of formation of bacterial biofilm per B.cereus and S.aureus during the incubation time by the crystal violet method. Many factors in biofilm formation are also involved in inhibition. In our work we studied the inhibitory effect of salicylic acid on adhesion and planktonic growth of both species S.aureus and B.cereus (ten isolates). The results showed that different isolates of Bacillus cereus tested exhibited an ability to form and to join the tested materials compared to isolates of S.aureus. The number of cells attached to B.cereus reached% and S.aureus is % suspension. The analysis tested the inhibitory effect of salicylic acid has proved that the salicylic acid concentrations tested reduced bacterial growth planktonic S. aureus isolates and B.cereus with optical density values (DO) of ... ..and…. respectively. These results were correlated with a significant decrease in the formation of mature biofilms formed by different isolates studied, with% inhibition rate and% respectively, with a minimum inhibitory concentration (CMI) of 2.76 mM.
Keywords: Borne infections; S.aureus; B.cereus; Biofilm; salicylic acid